FINANCING RISKS OF MICRO, SMALL, AND MEDIUM ENTERPRISES (UMKM) WITH COOPERATION PATTERNS BETWEEN ISLAMIC BANK AND BAITUL MAAL WA TAMWIL (BMT) - Shomad, Abdul (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Islamic Credit Unions and Baitul Maal Wa Tamwil (BMT) are part of Islamic micro finance as an effort of lower class society empowerment which is operated based on profit and loss sharing principle and implements Islamic moral values and group solidarity. This research discusses characteristics of cooperation patterns between Islamic bank and BMT in financing UMKM costumers and who would bear the financing risks of UMKM be. This research is doctrinal and applies both statute approach and conceptual approach. The result of this research shows that the characteristics of cooperation patterns between Islamic bank and BMT in financing UMKM costumers are identified by applying mudharabah muqayyadah contract between Islamic bank and Baitul Maal Wa Tamwil as shahibul maal while customers as mudharib. It is shahibul maal to bear risks as capital owner.Keywords: financing, Islamic bank, Baitul Maal Wa Tamwil